On pointwise statistical convergence - Gökhan, A; Güngör, M (Indian Nat Sci Acad, 2002)
In this study, we introduce a notion of pointwise statistical convergence of sequences of realvalued functions. Furthermore we introduce the concept of a statistically Cauchy sequence for functional sequences and prove that it is equivalent to pointwise statistical convergence of sequence of real-valued functions.
Keywords: functional sequence; pointwise convergence; statistical convergence